Class and gender: social stratification of women in contemporary urban China - Tang, Yao (2015)
This thesis studies the method of gender social stratification and its circumstance in contemporary urban China. Firstly, a ‘social class schema’ is created after comparing the occupational classification in class schemas of Erikson-Goldthorpe-Portocarero and the Chinese Academy of Social Sciences, and taking into consideration of the Standard Occupational Classification system (2010). Later, each stratum is subdivided into three sectors to reflect the Chinese dualist system of state and market, and the divisions in the market. Based on this schema and the data sets from the Chinese Household Income Project, 2002 and 2007, the shares of each social stratum and the earnings distribution are discussed, especially gender comparisons and changes. Moreover, to further scrutinise the differences in the same social stratum and to observe the impact of the household on men and women, the principal component analysis is applied to create a direct and indirect ‘Social Class Index’ (SCI) for each observation. Both indices are comprehensive and combine many aspects of the social stratification. The indirect ‘SCI’ also reflects the impact of the household with a changed variable set. After inspecting the composition changes of the social groups constructed on direct and indirect ‘SCI,’ the adjusted social stratification of genders are illustrated.